Risk Factors for Victimization and the Impact of Victim Status on Perceptions of Police Legitimacy in Australia - Wiedlitzka, Susann (Victims & offenders, 2021)
Previous research highlights that important differences exist between victim groups, but the impact victim status can have on perceptions of police legitimacy remains underexplored. The following paper contributes to this body of literature by utilizing the National Security and Preparedness Survey (NSPS, 2011–2012) to explore the risk/protective factors for victimization and differences between prejudice motivated crime (PMC) victims, non-PMC victims and non-victims in the Australian context, using Multinomial Logit Regression models. This study provides new insights into key differences between victim groups and perceptions of government and police legitimacy in the victimization context.